Pexelizumab in ischemic heart disease: a systematic review and meta-analysis on 15,196 patients. - Testa, L; Van Gaal, W; Bhindi, R; Biondi-Zoccai, G; Abbate, A; Agostoni, P; Porto, I; Andreotti, F; Crea, F; Banning, A (2008)
OBJECT: Pexelizumab is a humanized monoclonal antibody inhibiting C5 complement. It has been postulated to improve outcomes in patients undergoing coronary artery bypass surgery and urgent reperfusion therapy for ST elevation myocardial infarction. We aimed at evaluating the risk/benefit profile of pexelizumab (bolus + infusion) versus placebo on top of current approaches in the management of patients with ST elevation myocardial infarction or undergoing coronary artery bypass. METHODS: We conducted a search of BioMedCentral, CENTRAL, mRCT, and PubMed without language restrictions (updated October 2007) for randomized controlled trials. Outcomes of interest were the risk of major adverse events (the composite of all-cause death, myocardial infarction, and thromboembolic stroke), the risk of single end points, and heart failure. RESULTS: Seven trials were included (15,196 patients: 7019 patients with ST elevation myocardial infarction and 8177 undergoing coronary bypass surgery). No benefit of adding pexelizumab was found in the overall analysis for major adverse events (OR 0.91 [0.76-1.09]; P = .29], death (OR 0.79 [0.61-1.03], P = .11], myocardial infarction (OR 1.04 [0.89-1.22]; P = .14), stroke (OR 0.95 [0.66-1.38]; P = .8), heart failure (OR1.0 [0.82-1.22]; P = .99), nor in the settings of patients with ST elevation myocardial infarction treated with mechanical or pharmacologic reperfusion therapy. Pexelizumab was associated with a 26% reduction of the risk of death in the setting of coronary artery bypass (OR 0.74 [0.58-0.94]; P = .01). The number needed to treat was 100. CONCLUSION: Our data ruled out the hypothesis of any benefit of adding pexelizumab on top of currently available therapies for ST elevation myocardial infarction. However, pexelizumab reduces the risk of death in patients undergoing coronary artery bypass grafting.